A combined experimental and theoretical study on vibrational spectra of 3-pyridyl methyl ketone. Issue 4 (20th April 2020) - Celik, Sibel; Alp, Meryem; Yurdakul, Senay
Abstract: Using some spectral methods and density functional theory calculations, a complete structural, vibrational, thermodynamic, electronic, nonlinear optical properties of 3-pyridyl methyl ketone have been evaluated. The Fourier transform infrared spectrum was obtained for the title molecule at room temperature. In the theoretical calculations, the Becke three Lee-Yang-Parr functional with 6-311++G(d, p) basis set was applied to carry out the quantum mechanical calculations. The infrared spectra were interpreted by using of normal coordinate analysis based on the scaled quantum mechanical force field. In addition, molecular electrostatic potential map, some thermodynamic parameters at different temperatures of compound were investigated.